The National SOM Survey 1988 - SOM Institute, University of Gothenburg (University of Gothenburg, 1991)
The questionnaire for the third study in the series of annual SOM-surveys was divided into six subject fields: Mass media, politics and society, energy and nuclear power, Sweden´s relation to other countries, residential environment and interests, and social background and music habits. The SOM surveys contains a core of questions asked in earlier SOM-surveys. New questions in SOM88 dealt with the respondent´s opinion on best coverage of specific issues in different mass media and their opinion on publication of names in connection with crimes, accidents and personal relationships. The respondents had to indicate if they agreed or disagreed with a number of statements about the way Swedish journalists do their work. A number of questions dealt with the hearings held by the Swedish parliamentary standing committee on the constitution in connection with the so called Ebbe Carlsson-affair. Other questions dealt with mass media coverage of foreign submarine offence of Swedish territory. Furthermore the respondents had to value the political parties concerning aid to developing countries, defence issues, and EC policy. There were also a number of questions concerning the respondent´s interest in theatre.

Purpose:

The main purpose is to establish time series that enable researchers to analyse how various changes in society affect people's attitudes and behaviour.

Detta är den tredje undersökningen i serien Riks-SOM, en nationell frågeundersökning med syfte att kartlägga den svenska allmänhetens vanor och attityder på temat samhälle, opinioner och medier.

1988 års undersökning består av sex sammanhållna delar: massmedier; politik och samhälle; energi och kärnkraft; Sveriges förhållande till omvärlden; boende och fritidsintressen; samt bakgrundsuppgifter.

Många av frågorna har ställts i tidigare SOM-undersökning, men ett antal frågor har tillkommit. Nya frågeställningar i Riks-SOM 1988 gäller vilket medium som bäst bevakar olika ämnen; medias publicering av namn i samband med brott, olyckor och människors personliga förhållanden; bedömning av hur svenska journalister sköter sitt jobb; konstitutionsutskottets utfrågningar; massmedias behandling av ubåtskränkningarna; partiernas politik inom områdena biståndsfrågor, försvarsfrågor och EG-frågor; samt vilken form av teater man föredrar.

Genom att frågor ställts på ett likartat sätt över tid finns det i SOM-serien tidsserier om bland annat medieanvändning, politik, kärnkraftsopinion och förtroende för olika samhällsinstitutioner och grupper.

Syfte:

Huvudsyftet är att etablera tidsserier som gör det möjligt att analysera hur olika samhällsförändringar påverkar människors attityder och beteenden.
Den nationella SOM-undersökningen 1988
Riks-SOM 1988
Keywords: elections; val; mass media; massmedia; defence; försvar; participation; deltagande; public sector; offentlig sektor; international relations; internationella relationer; energy; energi; environment; miljö; leisure time; fritid; quality of life; livskvalitet; political interest; politiskt intresse; nuclear energy; kärnkraft; newspaper readership; tidnings läsekrets; membership; medlemskap; state control; statlig styrning; television news; tv-nyheter; theatre attendance; teaterbesök; radioactive wastes; radioaktivt avfall; equipment; utrustning; local press; lokalpress; professional ethics; yrkesetik; foreign policy; utrikespolitik; privatization; privatisering; economic conditions; ekonomiska villkor; risk; risk; internal politics; inrikespolitik; political parties; politiska partier; political leaders; politiska ledare; leisure time activities; fritidsaktiviteter; organizations; organisationer; CORS; CORS; Media; Media; Environment and conservation; Miljö och naturvård; Energy and natural resources; Energi och naturresurser; Political behaviour and attitudes; Politiska beteenden och attityder; International politics and organisations; Internationell politik och organisationer; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap